Space Occupying Lesion- Uncovering the Hidden Pathology of the Brain: A Case Report - Mukul Sharma; Afsar Jahan; Biplab Rath; Sudipta Ranjan Singh; Manoj Kumar Mohanty (Institute of Medico-legal Publications Pvt Ltd, 2021)
Sudden deaths as a result of undiagnosed primary intra-cranial lesions are the rarest of rare. A brought deadcase of 32-year-old female with past history of headache without any clinical diagnosis was found to be thecase of “transitional meningioma with focal rhabdoid differentiation which is histo-pathologically classifiedas WHO Grade 1 intra cranial lesion1. A complete autopsy including gross findings, internal findings withhistopathology and immuno-histochemistry can help us to diagnose the missed pathology to conclude thecause of death. It will also give the idea about autopsy-based statistics of these rare intra-cranial lesionswhich would help us to focus the cases with the history of headache to diagnose early with interventions andinvestigation including MRI or CT scan during life.